Hyperlocal Visual Content and Audience Engagement: A Comparative Study on Instagram (Developing a Conceptual Model for Digital Branding) - Raden Wahyu Utomo Martianto; Archita Desia Logiana; Teja Endra Eng Tju (Universitas Telkom, 2026)
The digital age has transformed culinary marketing strategies, with social media, particularly Instagram, becoming the primary platform for building audience engagement through visual content. Hyperlocality in visual communication not only emphasizes geographic location, but also integrates elements of culture, tradition, and community identity. Previous studies have shown that visual storytelling can increase engagement, but research on how hyperlocal visual content specifically affects audience engagement is still limited. This study uses a qualitative approach with visual analysis methods, in-depth interviews, and participatory online observation to explore hyperlocal visual content strategies in culinary marketing on Instagram. A comparative study was conducted on two Instagram accounts, @jajan.sawangan and @sawangankuliner, to understand how visual elements such as composition, color, typography, and narrative influence engagement. The results showed that using visual elements that are more aesthetically pleasing, consistent, and reflective of local identity can significantly increase audience engagement. Accounts with more structured visual strategies and stronger narratives have higher levels of interaction than accounts with less cohesive visual approaches. Based on these findings, the study developed a conceptual model of audience engagement with hyperlocal visual content that can be used to guide community-based digital branding strategies. This study contributes to the study of digital communication, hyperlocal marketing, and social media branding, and provides recommendations for culinary business professionals to optimize visual strategies on Instagram.